Obispos, clérigos y fieles en pie de guerra, Antioquia, 1870-1880 (2010)
ABSTRACT: This paper studies the Catholic Church situation in Antioquia in their relationships with the state and the society during the 1870’s decade and his decisive role in the civil war of 1876-1877. This paper show the fortifying process of the regional church in the context of the stresses of the Catholic Universal Church with the liberalism, founded in his cohesion ties, his Catholics mentalities and his positive relations with the Conservator State of Antioquia. This paper analyzes the inequality motivations, attitudes and comportments of bishops, clergy and a part of their faithful during and after the civil war. With the battles the government of the radical liberalism get week and the independent liberalism and conservatism get strong. The latest, protected by church, were able to establish in 1886 a central regimen, procatholic, pro-spanic and conservator.